Mitigasi Bencana Banjir Oleh Mahasiswa MBKM Proyek Desa Di Desa Ulanta Kabupaten Bone Bolango - Demulawa, Meilan; Buhungo, Trisnawaty Junus; Supartin, Supartin (-, 2025)
Disaster is an event or series of events caused by natural factors or non-natural factors and human factors that threaten and disrupt people's lives and livelihoods, causing human casualties, environmental damage, loss of property and psychological impacts. The aim of the Village Project MBKM program is to carry out a disaster mitigation program. For this disaster mitigation program, students work directly with all Ulantha village communities and village officials as well as the Regional Disaster Management Agency (BPBD) in making evacuation routes and boundaries for flood-prone areas. This study uses a type of descriptive research. As a result of this Disaster Mitigation Program, MBKM Physics Education students for VILLAGE PROJECT collaborated with the Regional Disaster Management Agency (BPBD) so that the evacuation routes are safe and easy for the community to find when there is a major flood. Through the socialization of Disaster Mitigation is an education to the community, so that the community knows the right solution related to the problem of flooding and becomes an amplifier of the dangers from the impact of flooding.